2011
DOI: 10.1017/s1759078711000328
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and linearity analysis of a burst mode RF PA with direct filter connection

Abstract: Burst mode operation is proposed as an efficiency improving technique for power amplifiers. The core idea is to modulate the amplitude of the envelope signal into a series of square-wave pulses such that the width of the signal burst or the total amount of pulses are varied according to the envelope. The phase information is still contained by the timing of the pulses. This work presents the efficiency and linearity analysis of burst mode radio frequency (RF)/power amplifier (PA). In addition, the efficiency p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This out-of-band energy possibly violates spectral mask requirements of the wireless standard. Dissipating the out-of-band energy, reduces the efficiency and a similar efficiency-versus-output power curve as the square root behaviour in class B condition would be the result [33][34][35][36]. These extra requirements to improve efficiency, out-of-band impedance and the spectral mask requirements, result in an increase of the cost of the bandpass filter at the output.…”
Section: Digital Polar Modulation and Burst Mode Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…This out-of-band energy possibly violates spectral mask requirements of the wireless standard. Dissipating the out-of-band energy, reduces the efficiency and a similar efficiency-versus-output power curve as the square root behaviour in class B condition would be the result [33][34][35][36]. These extra requirements to improve efficiency, out-of-band impedance and the spectral mask requirements, result in an increase of the cost of the bandpass filter at the output.…”
Section: Digital Polar Modulation and Burst Mode Operationmentioning
confidence: 99%
“…Also coding can be helpful to reduce the generated out-ofband power. As proof of concept, this has been implemented in [31,33,[35][36][37][38].…”
Section: Digital Polar Modulation and Burst Mode Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order not to degrade efficiency too much, those bursts should be long enough [5], [10], [11]. As a rule of thumb, f c /f s should be at least 10 in any operating mode.…”
Section: Operating Modes and System Parametersmentioning
confidence: 99%
“…So, in order to protect the SMPA, the researchers inserted an isolator, at the expense of a substantial degradation of the system power efficiency. This interaction between the SMPA and the BPF was studied in [13], where the researchers observed that by changing the length of the connection between these two blocks, the performance changed but, the proposed zero length connection is strongly restrictive. Staying with the initial configuration, the complete system was tested and measured in [14], where the obtained 43% of drain efficiency (and further dropping at lower input power values) is quite far from the theoretical expectations.…”
Section: Introductionmentioning
confidence: 99%